Hoax Detection of Indonesian News Media on Twitter Using IndoBERT with Word Embedding Word2Vec - Pernanda Arya Bhagaskara S M; Sri Suryani Prasetiyowati; Yuliant Sibaroni (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Hoax is data that is added or deducted from the news that occurred. In the digital age, hoaxes are increasingly being spread, and people are very quickly affected by their spread, especially hoaxes circulating in Indonesian news media on social media. Disseminating information that has not been confirmed as accurate can cause public concern and anxiety. Virtual diversion has transformed into a correspondence key to begin thinking, talking, and moving around cordial issues. In this manner, exploration will be led by consolidating the IndoBERT model with the Word2Vec development highlight in arranging deception news in Indonesian news media. This model was constructed using K-Fold cross-validation to enhance model performance across extensive data sets. The information utilized comes from tweets shared on Twitter by the Indonesian public. The trials that have been carried out demonstrate that combining Word2Vec with IndoBERT is effective at detecting hoaxes, with an overall accuracy score of 88% for the entire dataset. This conclusion can be drawn from the classification results of Word2Vec with IndoBERT. Also, the best precision and incentive for every cycle is almost 99%. In addition, the study's objective is to identify hoax news in Indonesian news media disseminated via social media. This will encourage individuals to be more cautious when reading and disseminating news, as untrue information will significantly impact certain individuals.